Y² + 8y - 33 :
Break the expression into groups for formula ax²+ bx+c :
= (y²- 3y) + (11y - 33 )
Factor y from y² - 3y => y (y - 3)
Factor out 11 from 11 y - 33 => 11 (y - 3)
= y ( y- 3 ) + 11 ( y - 3 )
Factor out common term (y - 3 ) :
= ( y - 3 ) ( y + 11 )
hope this helps!
Answer:
All real numbers are solutions.
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
3x+2=2x+2+x
3x+2=(2x+x)+(2)(Combine Like Terms)
3x+2=3x+2
3x+2=3x+2
Step 2: Subtract 3x from both sides.
3x+2−3x=3x+2−3x
2=2
Step 3: Subtract 2 from both sides.
2−2=2−2
0=0
I'm 17 and I'm in my Junior year of high school.
-2y + 5z = -3
y = -5x - 4z - 5
x = 4z + 4
-2(-5(4z + 4) - 4z - 5) + 5z = -3
-2(-20z - 20 - 4z - 5) + 5z = -3
-2(-20z - 4z - 20 - 5) + 5z = -3
-2(-24z - 25) = -3
48z + 50 = -3
<u> - 50 - 50</u>
<u>48z</u> = <u>-53</u>
48 48
z = -1⁵/₄₈
x = 4(-1⁵/₄₈) + 4
x = -4⁵/₁₂ + 4
x = ⁵/₁₂
y = -5(⁵/₁₂) - 4(-1⁵/₄₈) - 5
y = -2¹/₂ + 4⁵/₁₂ - 5
y = 1¹¹/₁₂ - 5
y = -3¹/₂
(x, y, z) = (⁵/₁₂, -3¹/₂, -1⁵/₄₈)
Side lengths of triangle are (6.2v-5.5) cm, (8.5v-6.7) cm, and (6.6w+7.6) cm.
To find:
The expression which represents the perimeter of the given triangle.
Solution:
We know that perimeter of a triangle is the sum of all sides of a triangle.